Application of the capability approach to Indigenous People’s health and well-being: protocol for a mixed-methods scoping review - Anna Chiumento; Catharina van der Boor; Carlos Iván Molina-Bulla; Ross G White (BMJ Open)
Background Indigenous Peoples are subject to marginalisation, and experience systematic disadvantage in relation to health outcomes. Human development initiatives may help determine whether, and how, Indigenous Peoples are able to be agents of their own development and improve their health and well-being. This scoping review protocol outlines a process for synthesising the existing evidence that has applied the capability approach (CA) to Indigenous People’s health and/or well-being.Methods and analysis A mixed-method scoping review is proposed including academic peer-reviewed publications and grey literature. Screening inclusion criteria will include Indigenous populations, using the CA approach to conceptualise health and/or well-being, and be available in English, Spanish, French or Portuguese. Publications that meet these criteria will undergo data extraction. Qualitative and quantitative data will be thematically and descriptively analysed and interpreted.Ethics and dissemination The proposed scoping review does not involve collecting data directly from Indigenous Peoples but will be based on previous research conducted within Indigenous settings. The current protocol and the proposed scoping review incorporate aspects of community involvement to guide the research process.This scoping review constitutes the first phase of a wider participatory action research project conducted with the Indigenous Kankuamo Peoples of Colombia. The findings of this review will be reported to local partners, published in a peer-reviewed journal and an executive summary will be shared with wider stakeholders. Within the wider project, the review will be considered alongside primary data to inform the development of tools/approaches of mental health and well-being for the Kankuamo communities.